Analyse De La Variation Morpho-Phenologique Et Genetique De Vingt Accessions Du Ble Dur Algerien (Triticum durum D.E.S.F.) - Belattar, Rima; Boudour, Leila; Chaib, Ghania (European Scientific Journal, ESJ, 2016)
Durum wheat (Triticum durum Desf.) is a strategic culture in Algeria. Characterization and evaluation of crop varieties allow backup and restoration of this genetic heritage and its use in breeding programs. In this context, the study is subject to the identification of some morpho - phenological parameters and molecular markers in kind RAPD variability of 20 genotypes of collection of Algerian durum wheat (Triticum durum Desf.) Belong to two varieties (rechenbachi and leucomelan). The results of the morpho-phenological and genetic analysis show substantial phenotypic diversity between varieties. RAPD marker showed an intervarietal genetic polymorphism.